Valoración de riesgo en el municipal de Aipe, Huila año 2014 (2014)
In this work different activities that can be carried out for the identification and assessment of risk factors to which workers Municipal Aipe file-Huila, where it is also important to provide an overview of the importance of the exposed arise safety and health at work in companies from the point of view of prevention. In its structure are different chapters within which specified in detail the general characterization of the institution subject, description of the problem situation, contextual diagnosis, objectives, rationale, target population, methodological and procedural issues, legal framework, theoretical framework, results conclusions and recommendations. Additionally there are some attachments that can expand those chapters.